Endothelial-to-Mesenchymal Transition in Pulmonary Hypertension. Issue 11 (17th March 2015) - Ranchoux, Benoît; Antigny, Fabrice; Rucker-Martin, Catherine; Hautefort, Aurélie; Péchoux, Christine; Bogaard, Harm Jan; Dorfmüller, Peter; Remy, Séverine; Lecerf, Florence; Planté, Sylvie; Chat, Sophie; Fadel, Elie; et al.
<x xml:space="preserve">Abstract</x> Background— The vascular remodeling responsible for pulmonary arterial hypertension (PAH) involves predominantly the accumulation of α-smooth muscle actin–expressing mesenchymal-like cells in obstructive pulmonary vascular lesions. Endothelial-to-mesenchymal transition (EndoMT) may be a source of those α-smooth muscle actin–expressing cells. Methods and Results— In situ evidence of EndoMT in human PAH was obtained by using confocal microscopy of multiple fluorescent stainings at the arterial level, and by using transmission electron microscopy and correlative light and electron microscopy at the ultrastructural level. Findings were confirmed by in vitro analyses of human PAH and control cultured pulmonary artery endothelial cells. In addition, the mRNA and protein signature of EndoMT was recognized at the arterial and lung level by quantitative real-time polymerase chain reaction and Western blot analyses. We confirmed our human observations in established animal models of pulmonary hypertension (monocrotaline and SuHx). After establishing the first genetically modified rat model linked to BMPR2 mutations (BMPR2Δ140Ex1/+ rats), we demonstrated that EndoMT is linked to alterations in signaling of BMPR2, a gene that is mutated in 70% of cases of familial PAH and in 10% to 40% of cases of idiopathic PAH. We identified molecular actors of this pathological transition, including twist overexpression and vimentin phosphorylation. We demonstrated that rapamycin partially reversed the protein expression patterns of EndoMT, improved experimental PAH, and decreased the migration of human pulmonary artery endothelial cells, providing the proof of concept that EndoMT is druggable. Conclusions— EndoMT is linked to alterations in BPMR2 signaling and is involved in the occlusive vas cular remodeling of PAH, findings that may have therapeutic implications.